The psychological functioning of patients admitted to a rural western cape hospital following an episode of non-fatal suicidal behaviour: stress, coping and perceived social support - De Clerk, Carla Christina (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.